2005
DOI: 10.1563/1548-1336(2005)31[171:chaheo]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Histologic, and Histomorphometric Evaluation of Mineralized Solvent-dehydrated Bone Allograft (Puros) in Human Maxillary Sinus Grafts

Abstract: Demineralized freeze-dried bone allografts (DFDBA) have been successfully used alone or in composite grafts for many decades. Little research has been done on the effect of retaining the mineral content of bone allografts. This study histologically and histomorphometrically evaluated a new mineralized bone allograft material placed in human atrophic maxillary sinuses. Seven partially edentulous patients requiring sinus grafts before implant placement were selected for this study Their age range was 56 to 81 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
31
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 44 publications
8
31
1
1
Order By: Relevance
“…In this study, we used MCBA based on encouraging documented reports of new bone formation [21]. Our histological results were consistent with those of Noumbissi et al [22], Froum et al [23] and Schmitt et al [13]. Therefore, MCBA can be considered as a bone substitute material that is totally resorbed and replaced with autogenous bone, integrating well into the organism [23].…”
Section: Discussionsupporting
confidence: 82%
“…In this study, we used MCBA based on encouraging documented reports of new bone formation [21]. Our histological results were consistent with those of Noumbissi et al [22], Froum et al [23] and Schmitt et al [13]. Therefore, MCBA can be considered as a bone substitute material that is totally resorbed and replaced with autogenous bone, integrating well into the organism [23].…”
Section: Discussionsupporting
confidence: 82%
“…Overall, 55 studies were categorized at level I 12–66 . Twenty‐six were level II, 67–92 nine were level III, 93–101 46 were level IV S1‐S46 (see references in http://www.joponline.org/doi/suppl/10.1902/jop.2016.150512/suppl_file/150512_supapp1.pdf and http://www.joponline.org/doi/suppl/10.1902/jop.2016.150512/suppl_file/150512_supapp2.pdf in online Journal of Periodontology ), and 53 were level V S47‐S99 (see references in http://www.joponline.org/doi/suppl/10.1902/jop.2016.150512/suppl_file/150512_supapp1.pdf and http://www.joponline.org/doi/suppl/10.1902/jop.2016.150512/suppl_file/150512_supapp3.pdf in online Journal of Periodontology ). The levels of evidence of each type of bone graft and summary of the RCTs are presented in http://www.joponline.org/doi/suppl/10.1902/jop.2016.150512 in online Journal of Periodontology .…”
Section: Resultsmentioning
confidence: 99%
“…These level I studies are summarized in http://www.joponline.org/doi/suppl/10.1902/jop.2016.150512/suppl_file/150512_suptab2.pdf in online Journal of Periodontology . There were eight studies 70,79,81‐86 and five studies 94,97‐100 that met level II and III criteria, respectively. The majority were level IV studies (21 studies) S1‐S21 (see references in http://www.joponline.org/doi/suppl/10.1902/jop.2016.150512/suppl_file/150512_supapp2.pdf in online Journal of Periodontology ).…”
Section: Resultsmentioning
confidence: 99%
“…Deproteinized bovine bone mineral (DBBM; Bio-Oss) is well documented as an augmentation material for sinus floor elevation. 15,17,[30][31][32][33] Using DBBM, Valentini and Abensur 17 found that newly formed bone increased from 21.1% to 27.6% at 6 to 12 months and a decrease of graft particle components from 39.2% to 27%. These data are comparable to the 27.3% residual graft proportion reported in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…2,17 Ample data have been reported on new bone formation in sinus floor elevation procedures; however, very few articles have dealt with the osteoconductive values of the grafted materials. 33,42,43 Proussaefs et al 42 found that 40.17% of the DBBM particle surface was in contact with bone, whereas Tadjoedin et al 43 found that only 34% to 38% of the DBBM surface was in contact with bone. Noumbissi et al 33 reported similar values for DBBM (34.75%) and higher values using a mineralized solvent dehydrated allograft (Puros).…”
Section: Discussionmentioning
confidence: 99%